Kemampuan Berfikir Kreatif Matematis Siswa SMP Melalui Proyek STEM Pada Model Fenomena Banjir - Rafina Eka Putri; Desventri Etmy; Risnanosanti Risnanosanti (Mandalika Mathematics and Educations Journal, 2026)
This study aims to describe the development of junior high school students' mathematical creative thinking abilities through a STEM project based on a flood phenomenon model. The mathematical creative thinking skills studied include four indicators: fluency, flexibility, originality, and elaboration. The study used a descriptive qualitative approach and was conducted at SMP Negeri 10 Bengkulu City in the even semester of the 2025/2026 academic year with 32 eighth-grade students divided into eight groups. Data were collected through observation, documentation, and semi-structured interviews, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that the STEM project based on flooding phenomena was able to facilitate the development of students' mathematical creative thinking skills. The fluency aspect was seen in students' ability to identify various factors causing flooding in a coherent and clear manner. The flexibility aspect was seen when students tried various alternative solutions and used measurement results as a basis for model improvement. The originality aspect emerged through model design ideas developed based on each group's thinking. Meanwhile, the elaboration aspect is evident in students' ability to explain in detail the design process, simulation, and analysis of measurement results. Thus, the flood-based STEM project learning provides a contextual, meaningful learning experience that supports the development of students' mathematical creativity.